PENGEMBANGAN MEDIA PEMBELAJARAN HYBRID MENGGUNAKAN LEARNING MANAGEMENT SYSTEM DI SMK MUHAMMADIYAH 2 MALANG - Aditya, Christian Sri Kusuma; Wiyono, Briansyah Setio; Setyaning Nastiti, Vinna Rahmayanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
Technological developments have impacted everyday life, including variations in learning using media. Hybrid learning is a learning model that combines face-to-face (offline) learning with online learning in a single, complementary system. One example of the application of hybrid learning is where students remain present in class for activities that require direct interaction, such as discussions, practicals, or exams, then the distribution of additional materials, assignments, and evaluations can be done through the Learning Management System (LMS) platform. However, hybrid learning media at the school level is still rarely used or has not been implemented evenly in many schools. Therefore, the aim of this community service program aims to produce e-learning-based learning media using the Learning Management System (LMS) at Muhammadiyah 2 Vocational High School (SMK) Malang so that the developed model will be relevant because it can adapt to technological developments and the need for learning flexibility.